Politics of African Peace Support Operation Architecture: What next post-2015 African Standby Force?. Issue 4 (2nd October 2017) - Onditi, Francis; Okoth, Pontian G.
ABSTRACT: Peace support operation (PSO) institutions were established to support the African peace and security architecture in developing integrated capacities (civilian, police and military) for deployment in crisis situations. This institutional development is part of the transition from the Organisation of African Unity to the African Union (AU) within the Constitutive Act of 2000. Drawing from both operational and strategic challenges facing African Standby Force structures, this article explores the implications of civil-military dissonance on the attainment of integrated capacities, post-2015 peace and security arrangement. The study posits that whereas the PSO institutions have made significant gains in increasing their regional visibility, tensions between the military and civilians systematically edges out the latter from the centre of decision-making. Moreover, while AU bureaucrats superficially assert that PSO institutions have made efforts towards developing integrated capacities, cogent and deeper analysis shows this is not the case; instead the heightened civil-military tension is a reflection of decision-making dilemmas facing both the military executives and political elites. The article concludes by proposing a review of African PSO norms, doctrines, and policies in order to develop an incremental strategy towards achieving full operational capacity that is inclusive of civilians and police.